Biochemical characterization of a novel hyperthermophilic α-l-rhamnosidase from Thermotoga petrophila and its application in production of icaritin from epimedin C with a thermostable β-glucosidase. (June 2020) - Xie, Jingcong; Zhang, Shanshan; Tong, Xinyi; Wu, Tao; Pei, Jianjun; Zhao, Linguo
Graphical abstract: Highlights: A novel thermostable rhamnosidase TpeRha was identified with high specific activity. A high productivity pathway for icaritin production was screened with TpeRha. A new co-conversion system (epmedin C to icaritin) with two enzymes was built. Abstract: Epimedin C, a major flavonoid extracted from Herba Epimedii, is a precursor of minor flavonoid icaritin that is a desired drug candidate with remarkable anti-cancer activities. For enhancing the biotransformation efficiency of icaritin, a novel α-l -rhamnosidase gene was cloned from hyperthermophiles Thermotoga petrophila DSM 13995. TpeRha displayed optimal activity at a pH of 4.5 and a temperature of 90 °C. The Km and Kcat of TpeRha for p -nitrophenyl-α-l -rhamnopyranoside were 2.99 mM and 651.73 s −1, respectively. It displayed broad catalytic ability in cleavage of the outer and inner rhamnopyranosyl moieties on the C-3 carbon of epimedin C. Further, this enzyme was utilized to improve the efficiency of the co-conversion system in transforming epimedin C into icaritin, in combined with a thermostable β-glucosidase Tpebgl1. In addition, a transformation pathway (epimedin C -icariin - icariside I - icaritin) with a high efficiency for icaritin production was screened. After a two-stage transformation under optimized conditions (90 °C, pH 4.5, 80 U/mL of TpeRha and 1.2 U/mL of Tpebgl1), 1 g/L of epimedin C was transformed into 0.4337 g/L of icaritin within 150 min, with a corresponding molar conversion rate of 96.9 %. This is the first report of enzymatic transformation on preparing icaritin from epimedin C by using thermostable glycosidase.